Needs analysis of kelom geulis Ethno-STEM module oriented to creative thinking skills - Rizka Amalia; Ghullam Hamdu (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2026)
Creative thinking is an essential 21st-century skill, yet it remains under- facilitated in elementary science education. Current Ethno-STEM materials are predominantly theoretical, focusing on conceptual understanding while neglecting hands-on engineering activities. Operating within the needs analysis phase of Design-Based Research (DBR), this study employed a mixed-methods convergent parallel design to investigate these material shortcomings alongside actual field requirements. The study was conducted at SD Tamansari in Tasikmalaya, West Java, involving three fourth-grade educators experienced in elementary science and five fourth-grade students as participants. Data were concurrently collected through document analysis of three existing Ethno-STEM modules, questionnaires, and in- depth interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were processed using an interactive model consisting of data reduction, data display, and conclusion drawing. Document analysis revealed a severe deficit in existing materials, showing only 30% PjBL syntax availability and 25% creative thinking stimuli. Field data highlighted a critical pedagogical gap for teachers, who encounter severe barriers translating theoretical concepts into actionable projects due to a lack of practical guides. Furthermore, 85% of students expressed a strong preference for hands-on experiences, specifically desiring physical assembly tasks like cutting and constructing Kelom Geulis miniatures. These findings offer a significant theoretical and empirical contribution to ethnoscience education by mapping precise pedagogical gaps and validating that a craft-based engineering project can structurally foster the fluency, flexibility, and originality of students' ideas. Ultimately, this study provides a concrete foundational framework for developing a PjBL- based Kelom Geulis Ethno-STEM module to bridge these documented classroom needs.